Various Meanings of Harf Jar Min in Arabic Studies - Muhammad Rinal Saputra; Nur Laila; Shiyam Fajriyanti; Ahmad Hifni (LITTERATURA: Jurnal Bahasa dan Sastra, 2023)
This article discusses the various interpretations of the harf min in Indonesian by taking a number of examples of verses from the Koran. In the study of Arabic grammar, the harf min is one of the particles that plays a role in changing the final sound of every noun or ism that comes after it, both of nouns in the form of mufrad (singular) and mutsanna (dual) or plural (many). Harfu min is one of the harf jars, while nouns that come after it are called isim majrur. This research is expected to present a comprehensive understanding of the various meanings of harf min. The method used in this research is a qualitative method based on library research. The data sources used are the verses of the Koran, most of which are taken from juz 'amma. This article shows that the harf jar min generally means "of or rather than". However, on the other hand the word min has a variety of meanings other than simply "from or rather than", even in certain contexts it can be interpreted as "to" which is an antonym of the word "from". In addition, sometimes the harfu min is not interpreted at all to conform to the naturalness of the Indonesian language. It was also identified that harfu min in several cases was related to dzahir isim, isim dhamir, harf, and dzaraf. This article concludes that the context of the sentence and the words accompanying min are some of the factors that can give rise to the variety of meanings of harfu min.